A design for disassembly tool oriented to mechatronic product de-manufacturing and recycling. (January 2019) - Favi, Claudio; Marconi, Marco; Germani, Michele; Mandolini, Marco
Abstract: The easy disassembly of certain product components is a prerequisite to guarantee an efficient recovery of parts and materials. This is one of the first step in the implementation of circular economy business models. Design for Disassembly (DfD) is a particular target design methodology supporting engineers in developing industrial products that can be easily disassembled into single components. The paper presents a method and a software tool for quantitatively assessing the disassemblability and recyclability of mechatronic products. The time-based method has been implemented in a software tool, called LeanDfD, which calculates the best disassembly sequences of target components considering disassembly precedencies, liaisons among components, and specific properties to model the real condition of the product at its End-of-Life (EoL). A dedicated repository has been developed to store and classify standard times and corrective factors of each disassembly liaison and operation. This knowledge feeds the two LeanDfD tool modules: (i) product disassemblability module, which allows to carry out the time-based analysis and to improve the disassemblability performance of target components, and (ii) product recyclability module, which estimates the quantities of materials that could be potentially recycled at the product EoL. The LeanDfD tool functionalities have been defined starting from the means of the user stories and the developed tool framework, data structure, databases and use scenarios are described. A group of designers/engineers used the tool during a re-design project of a washing machine, considering the disassemblability as the main driver. The case study highlights how the proposed DfD method and tool are able to support the implementation of re-design actions for improving product de-manufacturability and EoL performance. The LeanDfD features aid engineers in making a quick and robust assessment of their design choices by considering quantitative disassemblability and recyclability metrics.